Pengaruh Lingkungan Kerja dan Keselamatan Kerja terhadap Kinerja Karyawan Bagian Produksi di PT. Cahaya Murni Borneo Timur - Ria Four Ladys Lumban Tobing; Suryati Eko Putro; Wahyu Rochana (Jurnal Publikasi Ilmu Manajemen, 2025)
The high number of workplace accidents in Indonesia's manufacturing industry, including 31 incidents at PT Cahaya Murni Borneo Timur between September 2022 and June 2023, emphasizes the importance of improving safety standards and creating a conducive work environment to support employee performance. This study aims to analyze the effect of work environment and work safety on the performance of production employees. The research method uses a quantitative approach with survey techniques on 55 randomly selected respondents. The results of the regression analysis show that the work environment has a significant effect on employee performance (t_hitung = 2.782 > t_table = 2.006; sig. 0.008), as well as work safety (t_hitung = 2.098 > t_table = 2.006; sig. 0.041). Simultaneously, both variables had a significant effect (F_count = 24.199 > F_table = 3.17; sig. 0.000) with a contribution of 48.2% to the variation in employee performance. These results emphasize the importance of improving the quality of the work environment and implementing optimal work safety to support productivity.